Pengaruh Good Corporate Governance, Corporate Risk, dan Capital Intensity Terhadap Tax Avoidance Perusahaan Sub-Sektor Perbankan yang Terdaftar di Bursa Efek Indonesia (BEI) - Ratih Juwita; Antoni Antoni (Journal of Financial and Tax, 2023)
Tax avoidance is a method of reducing tax legally with the aim of minimizing the tax burden by taking advantage of loopholes in the tax provisions of a country to maximize the amount of profit after tax, because in this case the tax is an element of profit reduction. This research aims to analyze the effect of Good Corporate Governance, corporate risk, and capital intensity on tax avoidance either partially or simultaneously. The population in this research is the banking sub-sector companies listed on the Indonesia Stock Exchange for the 2018-2021 period, totaling 43 companies. The method of determining the sample using the purposive sampling method with several predetermined criteria, there are 10 companies with observations for 4 years, so the sample in this research is 40 data. The analytical method used in this research is multiple linear regression analysis. The results show that partially Good Corporate Governance and capital intensity have no effect on tax avoidance, while corporate risk has an negative effect on tax avoidance. Simultaneously Good Corporate Governance, corporate risk, and capital intensity affect tax avoidance